Marine biovalley: Universiti Malaysia Sabah - Saleem Mustafa (Penerbit UMS, 2007)
The book explains the concept of UMS marine biovalley, discusses the importance of marine biodiversity, knowledge-based approach to management of marine ecosystem and public awareness programs in this area. The contents are disposed towards marine biodiversity showcase in the form of marine aquarium and museum of Borneo Marine Research Institute.